HR Architecture in Directorate of Production PT. Dirgantara Indonesia (The Indonesian Journal of Business Administration, 2021)
PT. Dirgantara Indonesia (Persero) is a company that established as a part of strategic effort of Indonesia state in air dimension. To support and survive in existing businesses, company needs to have competitive advantages, including those obtained from their human resources. Therefore, we need a model of human resources that is aligned between the business and the strategy implementation. The implementation of human resource management in this research is through the HR Architecture model. With this model, using a matrix of HR characteristics, companies can assess jobs that provide value to the company by paying attention to the described quadrant. Thus, the focus of development, investment and competency improvement is will get more focused. Based on this, in accordance to HR Architecture model for each quadrant, it is expected that the company will be able to adjust the employee relationship model, determine sustainable investment in human resources and focus on work that increases value and becomes a competitive advantage for the company. Keywords: alignment in strategy, competitive advantage, human resource, HR Architecture model